Method in metaphysics : Lonergan and the future of analytical philosophy - Beards, Andrew (Lonergan studies., 2008)
In the last few decades, analytical philosophers have rediscovered an interest in the subject of metaphysics. Surveying the contributions made by these philosophers, Method in Metaphysics initiates a critical dialogue between analytical metaphysics and the philosophy of Bernard Lonergan. It argues for a basic method in metaphysics, a method that arises from a critically grounded epistemology and cognitional theory. In addition, it serves as a much-needed overview and introduction to current trends in analytical metaphysics.Andrew Beards shows how Lonergan's philosophy can help to clarify not only particular issues in current debates but also the larger question of a basic method. He goes on to apply this method to topics at the forefront of discussions in contemporary philosophy - topics such as universals, tropes, events, causality, and the metaphysics of the self and the social. While the main focus of the study is on Lonergan and analytical philosophy, Beards also introduces the philosophies of Whitehead, Husserl, and Derrida into the debate. He brings Lonergan's critical realist philosophy into finely textured dialogue with a number of well-known contemporary metaphysicians such as Dummet, Putnam, Lewis, and Kripke.